Stimulate at Risk Dyscalculic Pupil to Learn a Number Sequence: A Single Case Study in LINUS 2.0 Numeracy Remedial Class in Sandakan, Sabah - Fu, Sai Hoe; Chin, Kin Eng (EDUCATUM Journal of Science, Mathematics and Technology, 2017)
This study aims to explore a single case of teaching a number sequence using a new idea which is known as “drawing your hands” in order to engage at-risk Dyscalculic pupils. This research incorporates active learning which based on the cognitive constructivism theory and Feuerstein’ Mediated Learning Experiences to derive a new teaching method. It was implemented at a primary school in Sandakan, Sabah. This is a qualitative study involving one mathematics teacher and one at risk Dyscalculic pupil from a national primary school. The data were collected via lesson observations, interviews, and document analyses. The finding revealed that this new teaching concept was practical to scaffold the at-risk Dyscalculic pupil to learn number sequence.